Utilization of Moringa Leaf Extract (Moringa Oleifera) against the Ectoparasite Zeylanicobdella sp. on Grouper Fish In In-Vitro - Maurid Raihan Syahrul; Wulandari Rika; Miranti Shavika; Putri Dwi Septiani; Muzahar Muzahar; Yulianto Tri; Bakkara Okto Rimandi; Irawan Henky (BIO Web of Conferences)
Grouper is a mainstay commodity for mariculture in Indonesia. One of the obstacles in cultivating grouper fish in floating net cages is the infection of the hirudinea sea leech Zeylanicobdella sp. Leech infection causes fish growth to be stunted and they may not even be sold. The aim of this research is to determine the effect of adding moringa leaf extract (Moringa oleifera) and its effective dose which can kill sea leeches. This research was carried out in November – December 2023 for 30 days located at the Pengujan Fish Seed Center (BBI), Bintan Regency, Riau Islands Province. This research includes making extracts using 96% ethanol solvent, qualitatively testing the active content of simplicia, probit analysis of extracts on Artemia salina test animals and testing extracts on the leech Zeylanicobdella sp. The graded extract doses used for the LC-50 test on Artemia salina are 20 ppm, 40 ppm and 60 ppm. Meanwhile, the dose for testing on the leech Zeylanicobdella sp. namely 10 ppm, 20 ppm and 30 ppm. Determination of dosage for leeches is based on the LC50-24 value. The research results showed that the percentage of water content was 81,73% and the total yield was 9.25%. The results of the phytochemical test showed that 96% ethanol was successful in attracting bioactive compounds such as alkaloids, flavonoids, saponins and tannins. The LC50-24 hour value shows that the dose of Moringa leaf extract that can cause 50% death of test animals is 30,549 ppm and the best dose that can kill Zeylanicobdella sp. leeches namely a concentration of 30,549 ppm.